2015
DOI: 10.1007/s10535-014-0483-9
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative defence under drought stress in a wheat stay-green mutant

Abstract: A wheat stay-green mutant, named tasg1, was generated using the mutagen ethyl methane sulphonate applied to wheat (Triticum aestivum L.) cv. HS2. A drought stress was imposed by controlling irrigation and sheltering plants from rain. The antioxidant defence was characterized in the flag leaves of the tasg1 and wild-type (WT). Compared with WT, tasg1 had higher reduced ascorbate/oxidized ascorbate ratio, reduced glutathione/oxidized glutathione ratio, and antioxidant enzyme activities during senescence under bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…AMF infection increased the GSH and GSSG content was also reported in previous study in plants (Wu et al 2006). Similar to drought stress, altered ratio of GSH/GSSG has been observed in plants under various stresses (Hefny and Abdel-Kader 2009, Radyuk et al 2009, Maheshwari and Dubey 2009, Tian et al 2015. Eltayeb et al (2011) observed greater protections against oxidative damage imposed by various environment stresses in transgenic potato with higher level of reduced glutathione.…”
Section: Effect Of Drought Stress and Amf On Antioxidative Enzymessupporting
confidence: 82%
“…AMF infection increased the GSH and GSSG content was also reported in previous study in plants (Wu et al 2006). Similar to drought stress, altered ratio of GSH/GSSG has been observed in plants under various stresses (Hefny and Abdel-Kader 2009, Radyuk et al 2009, Maheshwari and Dubey 2009, Tian et al 2015. Eltayeb et al (2011) observed greater protections against oxidative damage imposed by various environment stresses in transgenic potato with higher level of reduced glutathione.…”
Section: Effect Of Drought Stress and Amf On Antioxidative Enzymessupporting
confidence: 82%
“…In sorghum, stay-green hybrids produced 47% more biomass under terminal drought [ 118 , 119 , 120 ]. A new wheat stay-green mutant tasg1 showed an enhanced antioxidative capacity that leads to a delayed senescence and better drought resistance [ 121 ]. The efficient removal of ROS by the ascorbate-glutathione cycle under limited water conditions might be the key factor for the observed enhanced stress tolerance.…”
Section: Stay Green Traitmentioning
confidence: 99%
“…Some functional stay-green mutants exhibit enhanced antioxidant capacities (Prochazkova et al 2001), delayed senescence, and prolonged photosynthetic activities (Wang et al 2020). Tian et al (2015) reported that the wheat stay-green mutant tasg1 has a stronger antioxidant capacity than wild-type (WT) plants at the grain-filling stage and under conditions of drought stress. To date, however, there have been few studies that have examined the antioxidant physiology of stay-green soybean, particularly the dynamic expression of antioxidant enzyme isogenes during leaf senescence.…”
Section: Introductionmentioning
confidence: 99%